2020
DOI: 10.1016/j.aohep.2020.09.001
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and the liver: What do we know after six months of the pandemic?

Abstract: Despite liver injury in patients infected with severe acute respiratory syndrome (SARS) coronavirus (CoV)-2 (SARS-CoV-2) is associated with prolonged hospitalization, and liver dysfunction is mainly described in patients with severe viral disease. How liver abnormalities may affect virus infection is still unknown. Improved understanding of host genetics, lifestyle, underlying comorbidities and adequate follow-up of patients with liver damage are critical in the new scenario of the pandemic virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 12 publications
1
31
0
4
Order By: Relevance
“…Indeed, a broad spectrum of symptoms associated with COVID-19 has been identified. These range from asymptomatic disease to mild and moderate symptoms and severe symptoms associated with critical illness resulting in acute respiratory distress syndrome, respiratory failure or multiorgan dysfunction, and/or death [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a broad spectrum of symptoms associated with COVID-19 has been identified. These range from asymptomatic disease to mild and moderate symptoms and severe symptoms associated with critical illness resulting in acute respiratory distress syndrome, respiratory failure or multiorgan dysfunction, and/or death [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the extensive release of inflammatory mediators such as TNF- α , IL-6, and IL-10 is associated with increased mortality risk in COVID-19 patients [ 45 ]. Moreover, this cytokine storm may lead to liver dysfunction in these patients as elevated AST/ALT levels are widely reported in the literature [ 46 ]. The potential benefits of β S supplementation in COVID-19 could be investigated in future research.…”
Section: Discussionmentioning
confidence: 99%
“…Кроме того, частота гипербилирубинемии увеличивается в 1,7 раза среди пациентов с COVID-19, которые находятся в критическом состоянии, а косвенные маркеры поражения печени, включая гипоальбуминемию, были обнаружены в семь раз чаще у пациентов с тяжелой формой COVID-19. Безусловно, указанные особенности течения заболевания в стационарных условиях требуют определенной программы реабилитации после курса лечения [399]. Это является основанием для дальнейшего изучения вопроса и включении в консенсус по пост-COVID синдрому результатов не только оценки симптомов поражения печени в острой фазе заболевания, но и в отдаленном периоде [400].…”
Section: клиническая картинаunclassified